Relationship between a standardized tackling proficiency test and match-play tackle performance in semiprofessional rugby league players - Speranza, M. J.; Gabbett, T. J.; Johnston, R. D.; Sheppard, J. M. (International Journal of Sports Physiology and Performance, 2015)
Purpose: This study examined the relationships between tackling ability, playing position, muscle strength and power qualities, and match-play tackling performance in semiprofessional rugby league players. Methods: Sixteen semiprofessional rugby league players (mean ± SD age 23.8 ± 1.9 y) underwent tests for muscle strength and power. Tackling ability of the players was tested using video analysis of a standardized 1-on-1 tackling drill. After controlling for playing position, players were divided into "good tackler" or "poor tackler" groups based on the median split of the results of the 1-on-1 tackling drill. A total of 4547 tackles were analyzed from video recordings of 23 matches played throughout the season. Results: Maximal squat was significantly associated with tackling ability (rS = .71, P < .05) and with the proportion of dominant tackles (rS = .63, P < .01). Forwards performed more tackles (P = .013, ES = 1.49), with a lower proportion of missed tackles (P = .03, ES = 1.38) than backs. Good tacklers were involved in a larger proportion of dominant tackles and smaller proportion of missed tackles than poor tacklers. Conclusions: These findings demonstrate that lower-body strength contributes to more effective tackling performance during both a standardized tackling assessment and match play. Furthermore, players with good tackling ability in a proficiency test were involved in a higher proportion of dominant tackles and missed a smaller proportion of tackles during match play. These results provide further evidence of the practical utility of an off-field tackling assessment in supplying information predictive of tackling performance in competition.